A Transparency-oriented BPMN Model Inspection Checklist: From conception to expert evaluations - Santos, Juliana Conceição; Maciel, Rita Suzana Pitangueira; Leite, Julio Cesar Sampaio do Prado (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.15083, 2025)
Process modeling is a key component for the success of an information system. Ensuring the quality of these models is essential for developing effective systems, including accessibility, auditability, understandability, informativeness, and usability. This article presents the design and evaluation of the Transparency-oriented Process Checklist (TPC), a structured inspection instrument for BPMN models emphasizing transparency-related quality characteristics. The TPC was developed by analyzing and integrating items from two existing checklists (CMP and BPCheck), refining them based on transparency dimensions, and structuring it with 51 verification items. A comparative evaluation was conducted to assess the applicability and effectiveness of the TPC. The evaluation team was divided into two groups. One group used the TPC, while the other applied BPCheck to inspect a real-world BPMN model. The results demonstrated that the TPC facilitated the identification of more quality problems (21 vs. 17), achieved greater agreement with the predefined “Oracle” answers (68.63% vs. 36.36%), and received more favorable assessments regarding understandability and support for identifying auditability issues. These findings underscore the TPC’s potential as a valuable instrument for supporting the inspection for the enhancement of BPMN process models.